STARD—rapid screening for the 6 most common G6PD gene mutations in the Chinese population using the amplification refractory mutation system combined with melting curve analysis. Issue 17 (April 2018) - Fan, Zuqian; Weng, Xunjin; Huang, Guosheng; Pan, Zhijian; Long, Zhao; Fan, Qiongying; Tang, Weijun; Fang, Lin; Long, Ju; Hu, Tian; Huang, Yongxia; Sun, Lei
Abstract : Abstract: Dot-blot hybridization and high-resolution melting curve methods are used to detect G6PD gene mutations; however, the performance and throughput limitations of these methods hinder their use for screening large populations. For simple screening, we developed a novel approach called "Amplification Refractory Mutation System combined with Melting Curve Analysis (ARMS-MC), " which enables rapid and batch-based detection of the 6 most common G6PD mutations. In this method, we established 4 PCR reaction systems that can be used to detect the 6 most common G6PD mutations (c.95A>G, c.392G>T, c.871G>A, c.1024C>T, c.1376G>T, and c.1388G>A) in the Chinese population. The ARMS-MC method was evaluated with 174 cases of clinical G6PD-deficient samples, and the results were verified by direct sequencing at G6PD gene exons. The results showed that 170 samples had ≥1 of the 6 mutations, which accounted for 97.70% of all mutations. These results were consistent with the results of direct sequencing with 100% accuracy and specificity. Sequencing validation revealed other mutations in the 4 samples in which no mutation was detected by the ARMS-MC method. ARMS-MC provides a rapid, simple, inexpensive, and accurate screening method for detecting the most common G6PD mutations in Chinese people.